2011
DOI: 10.1242/jcs.088500
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile patterns of pituitary hormone gene expression change during development

Abstract: SummaryImportant questions in biology have emerged recently concerning the timing of transcription in living cells. Studies on clonal cell lines have shown that transcription is often pulsatile and stochastic, with implications for cellular differentiation. Currently, information regarding transcriptional activity at cellular resolution within a physiological context remains limited. To investigate single-cell transcriptional activity in real-time in living tissue we used bioluminescence imaging of pituitary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…tumorigenesis) at the individual cell level whilst maintaining adequate hormone release at the tissue level by facilitating continued responsiveness to stimuli Paszek et al, 2010). Using similar techniques, it has also been demonstrated that, during embryonic development, lactotroph transcription is pulsatile before stabilizing in neonates; this transition may coincide with terminal differentiation when non-lineage specific genes become silenced (Featherstone et al, 2011).…”
Section: Network Support Of Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…tumorigenesis) at the individual cell level whilst maintaining adequate hormone release at the tissue level by facilitating continued responsiveness to stimuli Paszek et al, 2010). Using similar techniques, it has also been demonstrated that, during embryonic development, lactotroph transcription is pulsatile before stabilizing in neonates; this transition may coincide with terminal differentiation when non-lineage specific genes become silenced (Featherstone et al, 2011).…”
Section: Network Support Of Transcriptionmentioning
confidence: 99%
“…The embryonic development of the lactotroph network has not been studied as differentiated lactotrophs are the last of the pituitary hormone cell types to develop, with only very few cells detected by immunohistochemistry before birth (Featherstone et al, 2011). There is evidence that cells which will differentiate into lactotrophs are present earlier in development , but in the absence of other markers for this cell type it is not possible to study the embryonic formation of the network.…”
Section: Lactotroph Cell Organizationmentioning
confidence: 99%
“…This is aided by the organization of most endocrine and nonendocrine cell populations into 3-dimensionally intermingled networks, with thyrotrophs being a notable exception [54,[57][58][59][60]. Through the integration and amplification of signaling processes, these homotypic pituitary networks govern the complex electrical and transcriptional dynamics required to generate a 'gain-offunction' in hormone release [54,[61][62][63][64][65][66]. While the mechanisms underlying intercellular/intranetwork communication remain poorly characterized, a role for cell-cell coupling via gap junctions has been invoked [61,65,67] (Fig.…”
Section: Anterior Pituitary Gland: Gap Junctions As a Long-range Signmentioning
confidence: 99%
“…In rodents, much of fetal development occurs during the second half of pregnancy, when prolactin secretion is low, and while prolactin mRNA can be detected in the fetal pituitary at approximately embryonic day 15.5 469 or 17.5, 470 2. GONADAL STEROIDS, PITUITARY AND HYPOTHALAMUS prolactin protein is not present until much later in gestation, 258 and prolactin is not detectable in the serum until soon after birth. 471 Hence, the placental lactogens are likely to be the major ligands for fetal prolactin receptors during gestation.…”
Section: Fetal Developmentmentioning
confidence: 98%
“…253 The full repertoire of transcriptional activators and repressors that specify lactotrophs has not yet been defined, but the cells derive from the pituitary lineage expressing the transcription factor Pou1f1 (also known as Pit1), as do somatotrophs and thyrotrophs, cells secreting growth hormone and TSH, respectively. 258 After birth, there is a rapid expansion of the number of lactotroph cells, which in mice increase exponentially from birth to 5 weeks of age but then remain static from 8 weeks of age in the absence of physiological change or tumors. 253 Recently, late-embryonic pituitary prolactin in the absence of POU1F1 has been described in mice with altered pituitary development, 256 possibly analogous with the Pou1f1-independent thyrotroph population that is found in the embryonic pituitary.…”
Section: Lactotroph Functionmentioning
confidence: 99%